Effect of conventional and sustained release sodium valproate on serum leptin and some liver function tests in epileptic patients - Sajid Kh Ameen; Faris A Ahmed (University of Mosul, 2019)
Objectives: To compare the effect between conventional and sustained released sodium valproate monotherapy on serum leptin, body mass index (BMI) and some liver function tests including serum alkaline phosphatase (ALP), alanine amino transferase (ALT), aspartate amino transferase (AST), albumin, total bilirubin (TB) and direct bilirubin (DB) in epileptic patients. Patients and methods: The study is a case control study. It included 40 epileptic patients on conventional sodium valproate at doses 400-800 mg per day, and 42 patients on sustained released sodium valproate at doses 500-1000 mg per day. Forty healthy subjects sex and age matched served as controls were also included in the study. Blood samples were taken from the patients and controls and analyzed for serum ALT, ALP, AST, albumin, total bilirubin and direct bilirubin. Serum leptin was also analyzed by using ElISA technique. Results: Serum leptin, ALT, ALP, AST and TB in epileptic patients treated by conventional sodium valproate were significantly (p < 0.05) higher than that in patients treated with sustained release sodium valproate. However, serum albumin was significantly (p < 0.05) lower than that in patients treated by sustained released sodium valproate. No significant change was noticed between the two patients groups for BMI and serum DB Conclusion: Sustained release sodium valproate may have less hepatotoxic effect and cause less weight gain than conventional sodium valproate. The reduced frequency of doses and the possibility of dosing flexibility may all improve compliance of the patients.